Eco-friendly nanosilver sunscreen synthesized using Kweni (Mangifera odorata Griff.) leaf extract - Maharini, Indri; Sani. K, Fathnur; Efendi, M. Rifqi; Maimum; Fitri, Zahwa Syuhada; Putri, Chessa Nasya (Proceedings Academic Universitas Jambi, 2025)
Background: Excessive exposure to ultraviolet (UV) radiation can cause premature aging, erythema, and increase the risk of skin cancer. Skin protection can be accomplished by applying sunscreen products. Nanosilver synthesized via green synthesis using kweni (Mangifera odorata Griff.) leaf extract has potential as an active sunscreen agent due to its ability to reflect, scatter, and absorb UV radiation, as well as its antioxidant activity. Objective: this study aims to synthesize eco-friendly silver nanoparticles using Kweni (Mangifera odorata Griff.) leaf extract through a green synthesis approach and to evaluate their Methods: The sunscreen activity test was conducted using nanosilver synthesized with aqueous kweni leaf extract as a bioreductant. The test solution concentrations were 100, 200, and 300 ppm. Measurements were carried out using a spectrophotometer within the wavelength range of 290–320 nm. The SPF value was calculated using the Mansur method. Results: The SPF values of nanosilver at concentrations of 100, 200, and 300 ppm were 32.98 ± 0.069, 33.036 ± 0.215, and 34.037 ± 0.278, respectively. Conclusion: Kweni leaf-based nanosilver sunscreen demonstrated high effectiveness with SPF values classified in the ultra category. These silver nanoparticles have promising potential for further development as a natural cosmetic product using a green nanotechnology approach.